Design of a Plant-Based Yogurt-Like Product Fortified with Hemp Flour: Formulation and Characterization - Marco Montemurro; Michela Verni; Carlo Giuseppe Rizzello; Erica Pontonio (Foods, 2023)
Plant-based milk alternatives have gained massive popularity among consumers because of their sustainable production compared to bovine milk and because of meeting the nutritional requests of consumers affected by cow milk allergies and lactose intolerance. In this work, hemp flour, in a blend with rice flour, was used to design a novel lactose- and gluten-free yogurt-like (YL) product with suitable nutritional, functional, and sensory features. The growth and the acidification of three different lactic acid bacteria strains were monitored to better set up the biotechnological protocol for making the YL product. Hemp flour conferred the high fiber (circa 2.6 g/100 g), protein (circa 4 g/100 g), and mineral contents of the YL product, while fermentation by selected lactic acid bacteria increased the antioxidant properties (+8%) and the soluble fiber (+0.3 g/100 g), decreasing the predicted glycemic index (−10%). As demonstrated by the sensory analysis, the biotechnological process decreased the earthy flavor (typical of raw hemp flour) and increased the acidic and creamy sensory perceptions. Supplementation with natural clean-label vanilla powder and agave syrup was proposed to further decrease the astringent and bitter flavors. The evaluation of the starter survival and biochemical properties of the product under refrigerated conditions suggests an estimated shelf-life of 30 days. This work demonstrated that hemp flour might be used as a nutritional improver, while fermentation with a selected starter represents a sustainable and effective option for exploiting its potential.